Oil pipeline hydraulic resistance coefficient identification. Issue 1 (1st January 2021) - Bekibayev, Timur; Zhapbasbayev, Uzak; Ramazanova, Gaukhar; Bossinov, Daniyar
Abstract: The purpose of the study is to identify the hydraulic resistance coefficient of the main oil pipeline. Oil transportation through pipelines is the most efficient way to deliver oil from suppliers to consumers. The volume of transported oil depends on the pipeline hydraulic resistance. In practice, the hydraulic resistance coefficient is determined by the value of the Reynolds number and the pipeline internal surface roughness. The Reynolds number depends on the oil viscosity, which changes in a non-isothermal pipeline due to the heat exchange of the oil flow with the environment. The pipeline internal surface roughness changes during main oil pipeline operation. The identification of the pipeline hydraulic resistance coefficient is necessary for accurate calculations of the technological modes of the main oil pipeline. The SCADA (supervisory control and data acquisition) system determines the actual oil data (pressure, temperature, flow rate) along the main oil pipeline length in real time. Based on the results of the thermal-hydraulic calculations and the SCADA system, the hydraulic resistance coefficient identification method was built. The methodology was tested in the OPS-3—Koschagil, Severnye Buzachi—Karazhanbas, Prorva—Kultumiyev, Kassymov—Bolshoi Chagan main pipeline sections. The approbation results have shown sufficient accuracy in identifying the hydraulic resistance coefficient of oil pipelines. The obtained hydraulic resistance coefficient dependences were used to determine the oil transportation technological modes in industrial pipelines.